The City as the Classroom: The Case of “Start ‘em Young Advocacy” at Silliman University, Philippines - Maestrecampo, Novee Elarmo, Jr.; Macahig, Giovanni Tuballa (UI Scholars Hub, 2025)
This case study highlights the value of engaging with communities as real-world environments for practical and reflective learning. It suggests that students can develop insights and acquire knowledge through interactions with diverse groups and locations, even within urban settings. The paper presents the experience of implementing the “Start ‘em Young Advocacy,” a student-led, environment-focused, and project-based initiative within the Civic Welfare Training Service (CWTS) under the National Service Training Program (NSTP) at Silliman University, Philippines. In collaboration with the City Social Welfare and Development Office (CSWDO), CWTS students worked with thirty daycare centers. Using Kolb’s Experiential Learning Theory as a framework, this study explores student learning outcomes based on their written reflections, applying the “Head, Heart, and Feet” model. The results suggest that involvement in this program contributes to developing knowledge and skills, shifts in attitude and emotion, and forming future plans or initiatives. Overall, this paper presents urban environments as active learning spaces that support student development and provide opportunities to contribute to the United Nations Sustainable Development Goals (UN SDGs).